Clinical presentation and long‐term outcome of patients with KCNJ11/ABCC8 variants: Neonatal diabetes or MODY in the DPV registry from Germany and Austria. Issue 7 (23rd July 2022) - Warncke, Katharina; Eckert, Alexander; Kapellen, Thomas; Kummer, Sebastian; Raile, Klemens; Dunstheimer, Desiree; Grulich‐Henn, Jürgen; Woelfle, Joachim; Wenzel, Sandra; Hofer, Sabine E.; Dost, Axel; Holl, Reinhard W.
Abstract: Objective: To describe clinical presentation/longterm outcomes of patients with ABCC8/KCNJ11 variants in a large cohort of patients with diabetes. Research Design and Methods: We analyzed patients in the Diabetes Prospective Follow‐up (DPV) registry with diabetes and pathogenic variants in the ABCC8/KCNJ11 genes. For patients with available data at three specific time‐points—classification as K + ‐channel variant, 2‐year follow‐up and most recent visit—the longitudinal course was evaluated in addition to the cross‐sectional examination. Results: We identified 93 cases with ABCC8 ( n = 54)/ KCNJ11 ( n = 39) variants, 63 of them with neonatal diabetes. For 22 patients, follow‐up data were available. Of these, 19 were treated with insulin at diagnosis, and the majority of patients was switched to sulfonylurea thereafter. However, insulin was still administered in six patients at the most recent visit. Patients were in good metabolic control with a median (IQR) A1c level of 6.0% (5.5–6.7), that is, 42.1 (36.6–49.7) mmol/mol after 2 years and 6.7% (6.0–8.0), that is, 49.7 (42.1–63.9) mmol/mol at the most recent visit. Five patients were temporarily without medication for a median (IQR) time of 4.0 (3.5–4.4) years, while two other patients continue to be off medication at the last follow‐up. Conclusions: ABCC8/KCNJ11 variants should be suspected in children diagnosed with diabetes below the age of 6 months, as a high percentage can be switched from insulin to oral antidiabetic drugs. Thirty patients with diabetes due to pathogenic variants of ABCC8 or KCNJ11 were diagnosed beyond the neonatal period. Patients maintain good metabolic control even after a diabetes duration of up to 11 years.